Interfacial Behavior of Pamam-Pcl Dendrimers and in Situ Spontaneous Formation of Gold Nanoparticles at the Toluene-Water and Air-Water Interfaces: Experimental and Theoretical Studies - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
Using pendant drop and Langmuir techniques, the interfacial behavior of hydroxyl terminated poly(amido amine) (PAMAM-OH) dendrimers of generation 4, modified with poly(epsilon-caprolactone) (PAMAM-PCL), were analyzed and characterized. The study was performed at the toluene-water and air-water interfaces using two different molecular weights of PAMAM-PCL. Using this method, the interfacial activity of the dendrimers is shown to depend on the chain length of the PCL blocks. Using the Gibbs equation, the driving force for the adsorption process at the toluene-water interface was found to be of an enthalpic nature. In addition, stable monolayers of PAMAM-PCL at the air-water interface were obtained. For this analysis, the elasticity and critical exponent of the excluded volume, nu, for the PAMAM-PCL spread monolayers were determined. Alternatively, when the pure water phase was changed to an AuCl4- aqueous solution for both interfaces, different behavior in the interfacial activity of PAMAM-PCL was detected. Moreover, the spontaneous formation of gold nanoparticles at room temperature, at both interfaces, was observed. This was confirmed by UV-vis spectra and atomic force microscopy (AFM) images. Finally, molecular simulations and electronic structure calculations helped us to gain insights on the behavior of the dendrimers at the toluene-water interface and the PAMAM-PCL-gold nanoparticle interactions, respectively. (C) 2016 Elsevier Ltd. All rights reserved.